Efficacy and safety profile of combining programmed cell death‐1 (PD‐1) inhibitors and antiangiogenic targeting agents as subsequent therapy for advanced or metastatic non‐small cell lung cancer (NSCLC). Issue 17 (16th July 2021) - Xu, Ziyi; Li, Teng; Hu, Xingsheng; Hao, Xuezhi; Xing, Puyuan; Li, Junling
Abstract: Background: Previous studies have demonstrated that PD‐1 inhibitors are effective in the treatment of advanced or metastatic non‐small cell lung cancer (NSCLC). However, whether the combination of PD‐1 inhibitors and antiangiogenic agents benefit advanced NSCLC patients as subsequent therapy remains unknown. In this study, we retrospectively reviewed the efficacy and safety profile of this combination strategy as subsequent therapy for NSCLC patients in a real‐world setting. Methods: A total of 30 patients with advanced NSCLC, who progressed after at least two cycles of platinum‐based chemotherapy or targeted therapy and subsequently received combination therapy with a PD‐1 inhibitor and antiangiogenic agent, were included in this study. The safety profile and efficacy were also investigated. Results: At the time of a median follow‐up period of 10.7 months, 28 patients had experienced progression of disease and 16 patients had died. The median progression‐free survial (mPFS) was 5.0 months (95% confidence interval [CI]: 3.179–6.821), and the median overall survival (mOS) was 14.3 months (95% CI: 8.912–19.659). The objective response rate (ORR) and the disease control rate (DCR) were 10.3% and 72.4%, respectively (0 complete remission, three partial responses and 18 stable disease in 29 patients with measurable lesions). Patients with PD‐L1 expression of at least 1% of tumor cells ( n  = 5) had relatively longer mPFS compared to those with PD‐L1‐negative tumors ( n  = 14), (11.6 months vs. 3.7 months). Treatment was suspended in two patients due to grade 3 immune‐related pneumonia and pancreatitis, respectively. No novel adverse events (AEs) or grade 4 AEs were observed. Conclusions: A combination of PD‐1 inhibitors and antiangiogenic targeting agents may be beneficial for patients with advanced or metastatic NSCLC as subsequent treatment, especially for patients with PD‐L1 protein expression positive, and treatment is well tolerated. Abstract : Multiple strategies for second‐line and later therapy has brought limited efficacy for NSCLC patients with advanced disease. Therefore, determining a novel regimen for this population is urgently required. This study provides further evidence for combining PD‐1 inhibitor and antiangiogenic targeting agents as an effective and safe subsequent therapy for advanced or metastatic NSCLC, by reviewing the records of 30 patients. After a median follow‐up time of 10.7 months, the mPFS was 5.0 months, and the mOS was 14.3 months. In total, 19 patients underwent PD‐L1 testing. Patients with PD‐L1 expression of at least 1% of tumor cells ( n  = 5) had relatively longer mPFS compared to those with PD‐L1‐negative tumors ( n  = 14), being 11.6 versus 3.7 months, although the difference was not significant. The study indicated that the combination of PD‐1 inhibitors and antiangiogenic targeting agents might be beneficial and safe for patients with advanced or metastatic NSCLC as subsequent treatment, especially for those patients that were PD‐L1 protein expression positive.